MENAKAR POTENSI DAN TANTANGAN DALAM MENGGAGAS TRANSMIGRASI LOKAL DI DAERAH ISTIMEWA YOGYAKARTA - Yuanjaya, Pandhu; Alfana, Muhammad Arif Fahrudin (Department of Public Administration, Universitas Negeri Surabaya, 2016)
This study aims to analyze the potentials and challenges of local transmigration in Yogyakarta Special Region. This study crucial to consider the population that is concentrated in the Yogyakarta City and Sleman Regency as areas more develop than others. This is mix method research. Data were collected by questionnaires, observations, interviews and secondary data analysis. This study focused on Sultan Ground (SG) and Pakualaman Ground (PAG) in the three regencys, Gunung Kidul, Bantul and Kulon Progo. The findings show that the SG and PAG, potential and worthy of being local transmigration destination areas. Land use in three districts varied such as: agriculture, farming and fisheries. Some of the challenges that must be resolved before this policy made include the completion status and land-use conflicts, acceptance of local residents and increase the skills capacity of migrants.